AN INVESTIGATION INTO STUDENTS’ PERCEPTIONS OF THE FLIPPED CLASSROOM IN LEARNING IELTS WRITING AT IELTS NHUNG TRAN CENTER - Hoang Phuong Thao (Trường Đại học Ngoại ngữ, Đại học Đà Nẵng, 2024)
Today, the traditional learning and teaching method in which students are expected to passively receive the knowledge being presented and teachers control everything is found insufficient by the educators. Therefore, many teachers, educators and researchers have tried a variety of methods to enhance students’ English proficiency and arouse their interests in learning English writing. The Flipped Classroom Model, which has been widely implemented in the educational setting, is one of these effective methods. This study investigated the students’ perceptions on experiencing flippedclassroom method in learning IELTS writing at IELTS Nhung Tran Center. The research found out some facts about the effectiveness of flipped-classroom method, the difficulties that students often encounter and the attitudes of students towards this method. From that point, some implications were introduced in order to enhance the quality of learning and teaching writing at IELTS Nhung Tran Center, leading to the better achievement in not only students’ writing skills but also their academic levels